Provider perspectives on HPV vaccine hesitancy in the post-COVID-19 era - Thao N. Hoang; Denny Fe G. Agana-Norman; Aylia S. Rizvi; Christine D. Hsu; Fangjian Guo; Victor Adekanmbi; Abbey B. Berenson (Human Vaccines & Immunotherapeutics)
While HPV vaccination is effective in prevention of many HPV-associated cancers, only 61.4% of US adolescents were up to date on their HPV vaccinations in 2023. In the period following the COVID-19 pandemic, a decrease in vaccine uptake was reported, along with a rise in vaccine hesitancy. This study aimed to understand these changes to HPV vaccination and vaccine hesitancy that occurred following the COVID-19 pandemic from providers’ perspectives. We conducted 1-hour interviews with 12 participants over video calls that were then de-identified and transcribed. Eleven out of 12 providers noticed changes in their patients’ attitudes toward vaccines after the onset of the COVID-19 pandemic. Many providers mentioned COVID vaccine hesitancy impacting the reputation of unrelated vaccinations. Other notable topics included an overwhelming volume of health information, polarization of viewpoints, and lack of trust in authority. Future research would include a larger, more diverse pool of provider participants, as well as incorporate patient interviews. The results of this study emphasize the need to promote health literacy and rebuild trust between patients and the healthcare system to combat vaccine hesitancy.